Лазерные установки в современных сварочных технологиях. Исследование и применение - Пилярчик, Я.; Банасик, М.; Дворак, Д.; Стано, С. (Автоматическая сварка, 2008)
The paper contains a review of laser welding research works conducted at Instytut Spawalnictwa (Poland). It also presents
the equipment and investigation related to the use of hybrid processes and describes application of two types of laser
groups, i.e. CO₂- and Nd:YAG lasers, in welding processes providing examples on the use of these technologies in
machine-building and automotive industries, as well as in welded tailored and tubular blanks.